SMC4, a novel tumor prognostic marker and potential tumor therapeutic target - Zhao, Zonglei; Wang, Xixiu; Ding, Yan; Cao, Xuefeng; Zhang, Xingyuan (Frontiers in Oncology, 2023)
The structural maintenance of chromosome 4 (SMC4) is a member of the ATPase family of chromosomes. The most widely reported function of SMC4, as well as the remaining subunits of whole condensin complexes, is compression and dissociation of sister chromatids, DNA damage repair, DNA recombination, and pervasive transcription of the genome. Studies have also shown that SMC4 plays an exceedingly essential role in the division cycle of embryonic cells, such as RNA splicing, DNA metabolic process, cell adhesion, and extracellular matrix. On the other hand, SMC4 is also a positive regulator of the inflammatory innate immune response, while excessive innate immune responses not only disrupt immune homeostasis and may lead to autoimmune diseases, but even cancer. To further understand the expression and prognostic value of SMC4 in tumors, we provide an in-depth review of the literature and several bioinformatic databases, for example, The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), Clinical Proteomic Tumor Analysis Consortium (CPTAC), The Human Protein Atlas and Kaplan Meier plotter tools, illustrating that SMC4 plays a vital role in the occurrence and development of tumors, and high expression of SMC4 seems to consistently predict worse overall survival. In conclusion, we present this review which introduces the structure, biological function of SMC4, and its correlation with the tumor in detail; it might provide new insight into a novel tumor prognostic marker and potential tumor therapeutic target.